Green Synthesis ZnO Nanoparticles Using Rinds Extract of Sapindus rarak DC - Demi Dama Yanti; Evi Maryanti (Journal of Science and Applicative Technology, 2021)
The green synthesis of ZnO nanoparticles was carried out using a natural capping agent, Sapindus rarak DC rinds extract at low-temperature calcination and environmentally friendly solvent. The mixture of Zn(CH3COO)2, NaOH, and rinds extract was sonicated for 4 h at room temperature. The calcination was carried out at low temperature, 95oC for 8 h, and resulted in pale brown powder. XRD and SEM were used to confirm the structure and to analyze the morphology of ZnO nanoparticles respectively. XRD pattern of ZnO nanoparticles was corresponding to JDCPS card no 36-1451 with hexagonal structure. The average crystal size of ZnO nanoparticles was calculated using the scherrer equation and the average size was about 35.8 nm. From this study, the extract of the rind of Sapindus rarak DC was found to be a natural capping agent to synthesis ZnO nanoparticles because Sapindus rarak DC contain a pythochemical compound to limit the interaction between crystal seeds.